Establishment and Quality Control Criteria for Population Culture Collection - Promising Strategy for Animal Genetic Resource Preservation - Ma, Yuehui; Guan, Weijun; Li, Xiangchen; He, Xiaohong; Pu, Yabin; Zhao, Qianjun; Jin, Dapeng; Wu, Shen; Lu, Taofeng; Su, Xiaohua; Bai, Chunyu (IntechOpen, 2011)
None